Hemiboea thanhhoensis (Gesneriaceae), a new species from northern Vietnam - Nguyen, Cuong Huu; Averyanov, Leonid Vladimirovich; Wen, Fang (Phytotaxa, 2019)
Before 2010, Hemiboea Clarke (1798: 18) included about 23 species and 5 varieties mostly in central, southern and southwestern China, northern Vietnam and southern Japan (Ryukyu Islands), with the highest species diversity in southern and southwestern China (Weber 2004, Li & Wang 2004). Over the last two decades, 11 new taxa have been found and described in southern and southwestern China: eight new species and one new variety from Guangxi province (Li 2004, Li & Liu 2004, Xu et al. 2010, 2012, Wen et al. 2011, 2013, Pan et al. 2012, Zhou et al. 2013), two new species from Yunnan (Zhang et al. 2014, Chen et al. 2018), and one from Guizhou (Li et al. 2018). Meanwhile, the genus Metabriggsia Wang (1983: 1) including two species was revised and merged within Hemiboea (Weber et al. 2011). Additionally, H. subcapitata var. pterocaulis Li (2004: 261) was assigned from a variety to a distinct species, namely H. pterocaulis (Z.Y.Li) J.Huang, X.G.Xiang & Q.Zhang in Huang et al. (2017: 8) based on extensive morphological, phenological and molecular studies.